Participación ciudadana y su incidencia en los procesos administrativos del GAD municipal del cantón Quevedo - Ferán Muñoz, Ángel Rolando (2024)
This research aims to know the incidence of citizen participation in the administrative processes of the GAD municipal of Quevedo. The types of research used were field and descriptive, comprised of three phases; The first consisted of interviewing a Councilor from the Quevedo canton and the President of the San Camilo parish, the second, in a survey of the presidents of the 11 parishes; and, the third, a survey of citizens. The results obtained allowed us to identify the shortcomings between the local government and citizen participation, evidencing that there are no public policies that involve this organization in the operational processes of the municipality, consequently, the active participation of the parish presidents is observed, however, Their opinions and suggestions are not considered in the municipal ordinances. Finally, citizens perceive that citizen participation in different issues of social interest has not been strengthened, violating their rights. It is concluded that for there to be true citizen participation, it is important to strengthen public policies, create municipal ordinances that encourage more active participation and innovate the digital platform, in order to make administrative processes transparent and improve the interaction of citizens with the municipality.